Effect of adding of crushed leaves of thymus vulgaris and rosemary to the diet on productive performance of broiler (Journal of Hama University, 2022)
This study was carried to investigate the effect of adding of thymus and rosemary powder to broiler standard diet, on some productive performance. One hundred and four one-day old Ross strain unsexed chicks were randomly distributed into four groups (26 chicks for each) and each group were divided into two replicates (13 chicks for each), as flowing: First group is control without any addition, second and third groups included the addition of 1 g thymus powder/kg diet and 1 g rosemary powder/kg diet respectively, and the fourth group included the addition of mixture of one-gram thymus and one-gram rosemary powder/kg diet. The results showed significantly (P